EFFECTIVENESS OF BALLOON-BLOWING EXERCISE ON RESPIRATORY PARAMETERS AMONG CHILDREN WITH LOWER RESPIRATORY TRACT INFECTION - JISS MARY JAMES; LEANA PHEBE WILSON S (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was conducted to assess the effectiveness of balloon-blowing exercise on respiratory parameters among children with lower respiratory tract infection. Methods: A quantitative research approach and quasi-experimental (two-group pretest–posttest design) were adopted for this study. The sample size was 40 children with lower respiratory tract infection and used non-probability convenience sampling technique. Results: The results showed that the mean posttest score of respiratory parameters was 31 of the experimental group who were administered balloon blowing exercise with routine care which was higher than the control group posttest mean score of 23.35 having routine care and the t value was 4.21 (p<0.001) which showed that there was a significant difference in the post-test score of respiratory parameters in control and experimental groups. Conclusion: The study concluded that balloon-blowing exercise was effective to improve the respiratory parameters among children with lower respiratory tract infection.